Fading Spectrophotometric Quantification of Mesna in Commercial Injections with Ferric Salicylate Complex System - Ma, Wei-Xing; Cai, Ya-Wen; Liu, Ying-Hong; Sha, Ou (Asian Journal of Chemistry, 2013)
A new simple fading spectrophotometric quantification of mesna was developed, which based on the reaction of ferric solution with mesna (2-mercapto ethane sulfonate) to produce ferriferrous ion, whereas result from the red complex with the maximum absorption peak at 530 nm by the reaction of excess of ferric ion with sodium salicylate. The dependence of the absorbance on acidity, temperature and reaction time was investigated. In the diluted HCl solution, the decrease value of the absorbance (DA) at 530 nm, due to the presence of mesna was correlated with its concentration. Beer's law was obeyed in a mesna concentration range of 1-30 μg mL-1 with good correlation coefficient (0.9987). The proposed method was successfully applied to the quantification of mesna in commercial injections with the recoveries of the range from 99.68 % to 101.0 %.